Prioritising disclosures of information in analyst reports using the analytic hierarchy process: evidence from Malaysia - Mohd Thas Thaker, Hassanudin; Mohamad, Azhar (Inderscience Enterprises Ltd., 2019)
This paper aims to document investor priority of information disclosed in analyst reports which has not been extensively researched in the context of Malaysia. For the purpose of analysis, this study uses primary data via a survey method. The data is analysed using a versatile multi-criteria decision-making approach, known as the analytic hierarchy process (AHP). Findings reveal that investors place higher priority towards valuation in making an investment decision, followed by earnings summary, share performance, forecast revision, share information, financial indicators, segmental analysis, and scorecard in their use of the analyst report. The study is the first attempt to illustrate the priority of information disclosure in analyst reports given by investors when making an investment decision. Since this area of analyst recommendation is untapped in the context of Malaysia, the result of this study is expected to enrich the existing literature available in the field of analyst reports.